Increase of nectar bearing capacity of soft leaf stands - A. M. Sharygin; A. V. Krivtsova (Новые технологии)
One of the problems of forestry in the zone of coniferous-deciduous forests is the irrational use of sites occupied by softwood plantations of poor quality. The article presents the analysis of the nectar bearing production of soft-leaf plantations using the example of birch forests of the Bryansk region “Dubrovskoye lesnichestvo” in order to justify the possibility of its increase with the help of forest management measures. For this purpose, the task of determining the nectar bearing production by the vegetation tiers has been carried out at different fullness of the stand. It has been established that a significant biotechnological effect can be obtained with a strong intensity of dilution of high-density stands with an admixture of small-leafed linden, and the area occupied by similar low-density plantations should be taken into account when compiling the honey balance of the apiary.